2021
DOI: 10.1097/aln.0000000000003795
|View full text |Cite
|
Sign up to set email alerts
|

Patient Involvement in Anesthesia Decision-making: A Qualitative Study of Knee Arthroplasty

Abstract: Background Calls to better involve patients in decisions about anesthesia—e.g., through shared decision-making—are intensifying. However, several features of anesthesia consultation make it unclear how patients should participate in decisions. Evaluating the feasibility and desirability of carrying out shared decision-making in anesthesia requires better understanding of preoperative conversations. The objective of this qualitative study was to characterize how preoperative consultations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…25 A study characterizing how preoperative consultations for primary knee arthroplasty arrived at decisions about anesthesia found that most physicians presented the available options, recommended their preference, provided an opportunity for patients to voice their concerns, and ultimately, persuaded hesitant patient to accept their choice. 26…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 A study characterizing how preoperative consultations for primary knee arthroplasty arrived at decisions about anesthesia found that most physicians presented the available options, recommended their preference, provided an opportunity for patients to voice their concerns, and ultimately, persuaded hesitant patient to accept their choice. 26…”
Section: Resultsmentioning
confidence: 99%
“…26,35 Patients pointed to feeling unqualified or uninterested as reasons for having a more minor role in their medical care. 26 Instead, patients viewed consultations and decision aids as tools to prepare their expectations for anesthesia and ease their fears, but do not feel that the information influences their treatment decisions. 26,35 In our scoping review, a thorough search of the literature only resulted in 23 articles that exemplified community engagement among anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…79 Administration of spinal anesthesia without intraoperative sedation is uncommon in Western countries, 21 likely due to the desire of many patients to receive some degree of sedation or anxiolysis during surgery. 80 Notably, the Li et al 25 trial incorporated a protocol for neuraxial anesthesia in which no sedation was permitted to be administered during surgery. 47 No difference was found between this regimen and general anesthesia in postoperative delirium incidence or severity or other outcomes.…”
Section: Intravenous Sedationmentioning
confidence: 99%